-5u+45=-2(u-9)

Simple and best practice solution for -5u+45=-2(u-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5u+45=-2(u-9) equation:


Simplifying
-5u + 45 = -2(u + -9)

Reorder the terms:
45 + -5u = -2(u + -9)

Reorder the terms:
45 + -5u = -2(-9 + u)
45 + -5u = (-9 * -2 + u * -2)
45 + -5u = (18 + -2u)

Solving
45 + -5u = 18 + -2u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '2u' to each side of the equation.
45 + -5u + 2u = 18 + -2u + 2u

Combine like terms: -5u + 2u = -3u
45 + -3u = 18 + -2u + 2u

Combine like terms: -2u + 2u = 0
45 + -3u = 18 + 0
45 + -3u = 18

Add '-45' to each side of the equation.
45 + -45 + -3u = 18 + -45

Combine like terms: 45 + -45 = 0
0 + -3u = 18 + -45
-3u = 18 + -45

Combine like terms: 18 + -45 = -27
-3u = -27

Divide each side by '-3'.
u = 9

Simplifying
u = 9

See similar equations:

| 0.6(x-1)+0.2=6.6 | | -8(y-8)=2y-36 | | 2x-3=4-5x | | (6x^2+8x+12)-(4x^2+3x-2)= | | (3a^2-9a)+(12a^2+5a)= | | 13y-4y=27 | | (2+x)=(x*2) | | 2a+8=7a-5 | | 2.5*2x= | | 0.5x+12.3=7.1-1.1x | | (9x^2+6x+3)+(4x^2-8x+4)= | | 6c^2+21c-4c-14= | | (x+2)2+(y-6)2=25 | | 2x^2+5*2x= | | 3a(5a^2+8a)= | | -5x+7=3x+7 | | 14=6(y-2)+7y | | 6w+2(w+7)=30 | | 25+4y-1=16y-11-5y | | 4x+2y+z=166 | | 3+9x=7x+7-8 | | 5(u-3)-8u=-12 | | 108=LW | | -18n+12=-17n-14 | | A=15*12 | | -3x-10=5x+30 | | (-5xy)(2xy^2)= | | -4x-8=7 | | q/9=7/5 | | 10/7=5w | | 273729=72292 | | 8x^4-8= |

Equations solver categories